Neuroprotective Effects of Quercetin in Neonatal Hypoxic-Ischemic Brain Injury: A Meta-analysis - Can, Ceren; Hamilçıkan, Şahin (American Journal of Perinatology, 2025)
This study assesses the neuroprotective potential of quercetin in preclinical models of neonatal hypoxic-ischemic brain injury (HIBI) and its role as a possible enhancer of therapeutic hypothermia.A systematic review of 8 preclinical studies was conducted per PRISMA guidelines, sourced from PubMed, Scopus, and Web of Science, with a random-effects meta-analysis.Quercetin significantly lowered infarct volume, seizure susceptibility, and inflammation (pooled standardized mean differences [SMD] = 1.29; 95% confidence interval [CI]: 1.00–1.58; p < 0.001). Higher doses (>30 mg/kg, SMD = 1.65) and intraperitoneal (IP) administration (SMD = 1.42) outperformed lower doses or intravenous (IV) routes (SMD = 0.95). Rat models showed greater benefits (SMD = 1.38) than piglets (SMD = 0.85). Moderate heterogeneity (I2 = 45%) was noted, but sensitivity analysis confirmed robustness (SMD = 1.20). Publication bias was minimal (p = 0.12).Quercetin offers notable neuroprotection in neonatal HIBI, with an optimal 40 mg/kg IP dose, suggesting it could complement hypothermia. Limited bioavailability and lack of long-term data call for further research in advanced models.
Keywords: quercetin; neonatal hypoxic-ischemic brain injury; neuroprotection; meta-analysis; therapeutic hypothermia